Synthesis of Heteroxy Arylsulphide Alkanes and Their Antihistaminic Activity. - SHINDE, D.B.; SHINGARE, M.S. (Asian Journal of Chemistry, 2010)
A series of new substituted heteroxy bromo alkanes and substituted heteroxy arylsulphide alkanes have been prepared. The structures of these compounds were confirmed by spectral and analytical data. The heteroxy arylsulphide alkanes were screened for their antithistaminic activity by guinea pig chopped lung anaphylaxis method.